Application of the European Society of Cardiology, Adult Treatment Panel III and American College of Cardiology/American Heart Association guidelines for cardiovascular risk management in a French cohort of rheumatoid arthritis. (15th March 2015) - Tournadre, Anne; Tatar, Zuzana; Pereira, Bruno; Chevreau, Maxime; Gossec, Laure; Gaudin, Philippe; Soubrier, Martin; Dougados, Maxime
Abstract: Background: Patients with rheumatoid arthritis (RA) have greater rates of cardiovascular mortality and RA is an independent cardiovascular risk factor. For the management of cholesterol, the American College of Cardiology/American Heart Association (ACC/AHA) developed new guidelines for the general population. None of the European or American guidelines are specific to RA. The European League Against Rheumatism (EULAR) recommends applying a coefficient to cardiovascular risk equations based on the characteristics of RA. Our objective was to compare the three different sets of guidelines for the eligibility of statin therapy in RA-specific population with very high risk of cardiovascular disease. Methods and results: We calculated the proportion of patients eligible for statins according to the guidelines of the European Society of Cardiology (ESC), the Adult Treatment Panel III (ATP-III) and the ACC/AHA in a French cohort of statin-naïve RA patients at least 40 years age. Of the 547 women and 130 men analyzed, statins would be recommended for 9.1% of the women and 26.4% of the men, 15.6% of the women and 53.1% of the men, 38.8% of the women and 78.5% of the men, according to the ESC, ATP-III and ACC/AHA guidelines respectively. Conclusions: In RA patients, as has been observed in the general population, discordance in risk assessment and cholesterol treatment was observed between the three sets of guidelines. The use of the new ACC/AHA guidelines would expand the eligibility for statins and may be applied to RA population a condition at very high risk of cardiovascular disease.